Ancient self-refutation: the logic and history of the self-refutation argument from Democritus to Augustine - Castagnoli, Luca (Cambridge Univ. Press, 2010)
"A 'self-refutation argument' is any argument which aims at showing that (and how) a certain thesis is self-refuting. This is the first book-length treatment of ancient self-refutation and provides a unified account of what is distinctive in the ancient approach to the self-refutation argument, on the basis of close philological, logical and historical analysis of a variety of sources. It examines the logic, force, and prospects of this original style of argumentation within the context of ancient philosophical debates, dispelling various misconceptions concerning its nature and purpose and elucidating some important differences which exist both within the ancient approach to self-refutation and between that approach, as a whole, and some modern counterparts of it. In providing a comprehensive account of ancient self-refutation, the book advances our understanding of influential and debated texts and arguments from philosophers like Democritus, Plato, Aristotle, Epicurus, the Stoics, the Academic sceptics, the Pyrrhonists and Augustine"--